1994
DOI: 10.1111/j.1440-1819.1994.tb03020.x
|View full text |Cite
|
Sign up to set email alerts
|

A Schizophrenic Patient Who Developed Extreme Hypothermia after an Increase in the Dose of Haloperidol: A Case Report

Abstract: A patient with chronic schizophrenia, who had been treated for a long time with chlorpromazine, haloperidol, levodopa, benserazide hydrochloride, diazepam and biperiden, developed extreme hypothermia (about 32°C) when the dose of haloperidol was increased because of a deterioration of the patient's mental symptoms. No other physical manifestations were observed, except bradycardia. The turnover of noradrenaline in the cerebrospinal fluid and blood was increased in association with the hypothermia in this patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…However, anecdotal reports, caseseries studies and some small-sample, controlled animal studies (Adler and Geller, 1987 ;Boules et al, 2001 ;Catalina et al, 2002 ;Fjalland, 1979) and human studies (Eikenboom et al, 1997 ;Harada et al, 1994 ;Heh et al, 1988 ;Maeir et al, 1994 ;Shiloh et al, 2000 ;Yehuda, 1977) suggest that APDs can decrease body temperature, possibly via a direct effect on central (possibly hypothalamic) thermoregulatory effectors, or indirectly by reducing the levels of pyrogenic cytokines such as IL-1b, IL-6 and TNF-a (Kowalski et al, 2001 ;Monteleone et al, 1997). Since corneal temperature may correlate with core body temperature (Mapstone, 1968 ;Scott, 1988), our findings may further substantiate some of these previous reports which implied higher baseline core temperature in drug-free patients compared to APD-treated schizophrenia patients (Heh et al, 1988 ;Morgan and Cheadle, 1976 ;Shiloh et al, 2000Shiloh et al, , 2001.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, anecdotal reports, caseseries studies and some small-sample, controlled animal studies (Adler and Geller, 1987 ;Boules et al, 2001 ;Catalina et al, 2002 ;Fjalland, 1979) and human studies (Eikenboom et al, 1997 ;Harada et al, 1994 ;Heh et al, 1988 ;Maeir et al, 1994 ;Shiloh et al, 2000 ;Yehuda, 1977) suggest that APDs can decrease body temperature, possibly via a direct effect on central (possibly hypothalamic) thermoregulatory effectors, or indirectly by reducing the levels of pyrogenic cytokines such as IL-1b, IL-6 and TNF-a (Kowalski et al, 2001 ;Monteleone et al, 1997). Since corneal temperature may correlate with core body temperature (Mapstone, 1968 ;Scott, 1988), our findings may further substantiate some of these previous reports which implied higher baseline core temperature in drug-free patients compared to APD-treated schizophrenia patients (Heh et al, 1988 ;Morgan and Cheadle, 1976 ;Shiloh et al, 2000Shiloh et al, , 2001.…”
Section: Discussionmentioning
confidence: 97%
“…However, neuroleptictreated schizophrenia patients may also exhibit hypothermia (Heh et al, 1988 ;Laborit, 1979 ;Maeir et al, 1994 ;Schwaninger et al, 1998), a within-normal range decrease , or increase Shiloh et al, 2001) in core body temperature as well as various hyperthermic syndromes such as febrile catatonia, neuroleptic malignant syndrome (NMS) (Lazarus et al, 1989) or neuroleptic-related heat stroke (Dixit et al, 1997). Nevertheless, accumulating data indicate that APDs may also lower baseline core body temperature (within normal range) (Harada et al, 1994 ;Heh et al, 1988 ;Maeir et al, 1994 ;Shiloh et al, 2000 ;Yehuda, 1977) and especially during the initial hours/days of administration (Clark, 1979 ;Shiloh et al, 2000). It was even anecdotally suggested that the therapeutic effect of APDs might correlate with a decrease in core body temperature of schizophrenia patients (Heh et al, 1988), and that typical APDs might differ from atypical APDs by their diverse effect on core body temperature (Bauer and Gaertner, 1983 ;Wahlbeck et al, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…The references cited in their communication are so important that they are listed again here. [6][7][8][9][10][11] According to his family, the patient presented here was not known to be taking any antipsychotic or neuroleptic drugs, and no pill bottles were found on his person or in his hotel room.…”
Section: Hypothermia Due To Neuroleptic Drugsmentioning
confidence: 99%
“…Festzuhalten ist, dass Hypothermien im Zusammenhang mit der Gabe verschiedenster Antipsychotika mit unterschiedlichen Rezeptorprofilen sowohl für typische als auch atypische Substanzen beschrieben wurden [15,32,37].…”
unclassified